Uncertainty, FDI Inflows, and Financial Market Development: Empirical Evidence - Godfrey Marozva; Margaret Rutendo Magwedere (Economies)
This study offers insight into the multifaceted relationship between economic policy uncertainty, foreign direct investment, and financial development. It analyzes the effects of economic policy uncertainty and financial development on foreign direct investment (FDI) inflows, using a sample of 75 emerging markets and developing countries, over 2000–2023. To achieve this, a pooled mean group (PMG) was used, and the finding of this study for this period is a positive long-term relationship between economic policy uncertainty and foreign direct investments inflows, challenging the traditional view that uncertainty deters investment. In the long term, the joint effects of financial development and economic policy reduced foreign direct investments. These findings highlight the critical role of financial development in shaping the long-term impact of uncertainty on FDI, and they underscore the need for policy to enhance financial systems in order to stabilize and sustain FDI inflows in uncertain environments.